Bond between very-high and ultra-high performance fibre reinforced concrete and profiled deck sheeting. (15th July 2022) - Chen, S.; Visintin, P.; Oehlers, D.J.
Abstract: The behaviour of steel concrete composite slabs at all load levels is controlled by the shear transfer between the profiled steel deck and concrete slab. To apply new concrete technologies, such as high-strength and fibre-reinforced concretes, to steel concrete composite slabs, it is therefore essential to quantify the interfacial bond-slip properties. In this paper, a testing approach based on single-lap shear tests, commonly applied to quantify interfacial shear properties for external reinforcement, is applied to measure the bond between profiled sheets and concrete. The testing regime consists of 6 trial tests used as the basis for developing the test methodology and 48 tests to quantify the impact of concrete strength (very-high and ultra-high-strength), high volumes of steel micro fibres, and coarse aggregate, on the bond between concrete and dovetailed and trapezoidal profile decks. The results show that the concrete strength and the presence of coarse aggregate have limited impact on the bond properties, however the presence of fibres significantly improves bond strength and toughness for dovetailed profiled decks but has limited influence on trapezoidal decks. Highlights: Investigates the bond between profile sheets and ultra-high performance concrete. Considers the impact of coarse aggregate and fibres. Fibres significantly improve the strength and ductility of shear flow. Coarse aggregate can be added to UHPC without impacting shear flow.